El Excentrico, 1971-10-20 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
October 20, 1971 [20 de octubre de 1971]. No volume or issue number. Cover has photographs of 12 Model Cities Education Instructors.